Into the void: Re-envisioning silence in foreign language education through a socio-emotional learning lens - Pentón Herrera, Luis Javier (Neofilolog, 2024)
Historically marginalized and often misunderstood, silence has predominantly been viewed as a barrier to effective communication and engagement in educational settings. This paper argues for a re-evaluation of silence, viewing it not as an absence of speech, but as a potent tool for fostering deep learning, introspection, and emotional intelligence. By integrating social-emotional learning (SEL) principles, it is posited that silence can enhance, and is an essential element of, affective communicative competence (Pentón Herrera & Darragh, 2024), aiding the development of empathy, self-regulation, and a more profound connection to the language learning process. This conceptual paper explores the nuanced role of silence within the context of foreign language classrooms through a SEL lens. Traditional perceptions of silence are critically examined, a shift towards an asset-based view through SEL is proposed, and practical strategies for educators to incorporate silence meaningfully into their pedagogy are suggested. To conclude, perspectives on utilizing silence as a transformative element in SEL-driven language education are offered, aiming for a harmonious integration that enriches the teaching and learning experience.